Mengasah Kecintaan Membaca: Pengabdian dalam Kegiatan Literasi di Perpustakaan Sekolah sebagai Bagian dari Program MBKM - Aulia Rahmi; Akhmad Ali Mirza (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
The literacy program implemented at MTs Muslimat NU as part of the MBKM initiative addresses the low reading interest among students by fostering a sustainable reading culture. This program aimed to optimize the school library as a center of learning and increase students’ participation in literacy activities. Activities were structured to accommodate gender-specific groups, dividing each class into two sessions—one for female students and another for male students—conducted from Monday to Thursday. Each group participated twice weekly, engaging in reading exercises, book discussions, and digital literacy training. The methods involved collaborative planning with teachers and students of MBKM, surveys, and focus group discussions to identify the specific needs of the school community. The results demonstrated significant improvements in reading habits, as evidenced by a 30% increase in library visits and active participation in literacy clubs. Additionally, the program fostered the emergence of student leaders who encouraged their peers to engage in reading and critical discussions. This participatory approach proved effective in creating a dynamic literacy ecosystem and strengthening social cohesion within the school. The findings underline the importance of integrating literacy programs with active community participation and optimizing libraries as educational hubs, ensuring long-term benefits in developing reading skills and fostering a culture of knowledge-sharing.